Antibiotic susceptibility profiling in diabetic foot ulcer patients and evaluating treatment outcomes at a tertiary care hospital - Kumar, T. J. Prasanna; Ramineni, Hari Babu; Shaik, Reshma; Yellavula, Suma Navya; Chandra, Virajitha (International Surgery Journal, 2020)
Background: Diabetic foot infections are the predominant complications of diabetes mellitus with uncontrolled hyperglycemia levels. Multiple microbial invasion is the primary cause and the causative organism are aerobic gram positive cocci, gram negative bacilli such as Pseudomonas species, Escherichia coli, Klebsiella species, Proteus species and anaerobes. Methods: This is a prospective, observational study conducted in the Department of General Surgery. 50 patients constituted the sample in our study. Patients pus and wound swab samples were collected using sterile and moist swab sticks under aseptic conditions and processed. Results: More gram negative bacteria (66%) were isolated than gram positive bacteria (34%). E. coli (38%) is the major isolated microorganism. Among the isolated organisms many of them are susceptible to amikacin (60%), imipenem (52%) and ciprofloxacin (46%) respectively. Conclusions: E. coli is the most common cause of infection. The antibiogram study showed an incidence of multiple resistant microorganisms to commonly used antibiotics.